156 views
4 votes
Please explain steps to solve

Please explain steps to solve-example-1
User Sherita
by
6.1k points

2 Answers

4 votes

Explanation:

use formula to find hypotenuse


\sqrt{ {(a)}^(2) } + {(b)}^(2) = c

it will be

square root (11)² + (5)² = c

square root 121 + 25 = c

square root 146 = c

12.08 = c

LM = 12.08

User Vivek Aditya
by
6.3k points
4 votes

Answer:

11

Explanation:

To find LM we need PM. We can use the Pythagorean Theorem:

  • a^2+b^2=c^2
  • PN^2+PM^2=MN^2
  • 5^2+PM^2=11^2
  • 25+PM^2=121
  • PM^2=96
  • PM=√96

Now using the Pythagorean Theorem, we can find LM:

  • a^2+b^2=c^2
  • LP^2+PM^2=LM^2
  • 5^2+(√96)^2=LM^2
  • 25+96=LM^2
  • 121=LM^2
  • 11=LM

Or you could have seen that triangle LPM is congruent to triangle NPM by SAS (5, 90º, and PM) so LM=NM=11.

User Shazron
by
6.3k points